The Business To Business Marketing Strategies For The Package Delivery Service Companies To Increase The Volume Of Delivery - Yuary Farradia; Khaeruman; Fatari; Ismunandar (Publisher Cv. Inara, 2021)
In this study, the researchers used descriptive qualitative research methods with case study research on the object of research using observation, interviews, and documentation methods, data analysis techniques using SWOT analysis techniques (strengths, weaknesses, opportunities, threats) combined with IE Matrix to determine the position company.The results showed that the company uses a special tariff strategy and effective communication with customers. The IE Matrix analysis shows the company's position at a growth rate through horizontal integration, meaning that the company has the opportunity to expand the market, improve facilities, or merge with other companies in the same industry. From the results of the SWOT analysis, alternative strategies are obtained, namely: a) increasing the company's competitiveness and, b) competitive pricing policies with competitors that are adjusted to market prices.